2018
DOI: 10.5217/ir.2018.16.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Association of endoscopic and histological remission with clinical course in patients of ulcerative colitis

Abstract: Background/AimsThe therapeutic goal for treating ulcerative colitis (UC) patients has shifted to achieving mucosal healing over the past few years. However, at present, limited data is available on the correlation between endoscopic findings and histological remission in patients with endoscopic mucosal healing.MethodsThis was a prospective observational study conducted over a period of 18 months (January 2014 to June 2015) at Dayanand Medical College and Hospital, Ludhiana, Punjab, India. Patients diagnosed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 10 publications
(20 reference statements)
2
49
0
3
Order By: Relevance
“…To clarify that point, there is a need for periodic measurements of PGE-MUM to be performed in the same patient and prospective follow-up be performed of patients with relapse. In recent years, treatments aimed at histological healing more advanced than mucosal healing have also been required, and reports of the comparison between histological healing and biomarkers have been found [22][23][24][25]. Further studies are needed to determine if PGE-MUM could be a biomarker to predict histologic healing.…”
Section: Discussionmentioning
confidence: 99%
“…To clarify that point, there is a need for periodic measurements of PGE-MUM to be performed in the same patient and prospective follow-up be performed of patients with relapse. In recent years, treatments aimed at histological healing more advanced than mucosal healing have also been required, and reports of the comparison between histological healing and biomarkers have been found [22][23][24][25]. Further studies are needed to determine if PGE-MUM could be a biomarker to predict histologic healing.…”
Section: Discussionmentioning
confidence: 99%
“…These differences between studies may reflect the influence of the microbiome and/or the animals’ age, as previously reported in experimental DSS colitis[ 27 , 28 ]. In addition, it has been reported that UC patients in clinical and endoscopic based remission presenting with active histological inflammation possess a higher risk for clinical relapse[ 29 , 30 ]. In this way, our study may provide an understanding of the pathological and clinical response of severe human UC, with higher chances of relapsing and chronic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies have evaluated the role of eosinophils in UC. Narang et al 32 followed 76 Indian patients with UC in clinical remission. Of these patients, 60.5% (46/76) were in endoscopic remission (MES 1) and 32.7% (15/46) had histologic evidence of activity.…”
Section: Histology As a Predictor Of Clinical Outcomesmentioning
confidence: 99%